Reshaping national intelligence for an age of information - Treverton, Gregory F. (RAND studies in policy analysis., 2001)
In a bold and penetrating study, Gregory Treverton, former Vice Chair of the National Intelligence Council and Senate investigator, offers his insider's views on how intelligence gathering and analysis must change. Treverton suggests why intelligence needs to be contrarian and attentive to the longer term. Believing that it is important to tap expertise outside government to solve intelligence problems, he argues that involving colleagues in the academy, think tanks, and Wall Street befits the changed role of government from doer to convener, mediator, and coalition-builder. Hb ISBN (2001): 0-521-58096-X.